2016
DOI: 10.1073/pnas.1525022113
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA #32 contributes to antiviral responses by controlling interferon-stimulated gene expression

Abstract: Despite the breadth of knowledge that exists regarding the function of long noncoding RNAs (lncRNAs) in biological phenomena, the role of lncRNAs in host antiviral responses is poorly understood. Here, we report that lncRNA#32 is associated with type I IFN signaling. The silencing of lncRNA#32 dramatically reduced the level of IFN-stimulated gene (ISG) expression, resulting in sensitivity to encephalomyocarditis virus (EMCV) infection. In contrast, the ectopic expression of lncRNA#32 significantly suppressed E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 39 publications
(55 reference statements)
3
76
0
1
Order By: Relevance
“…Epigenetic mechanisms such as DNA methylation, histone modifications and non-coding RNAs emerge to play essential roles in gene-specific transcriptional regulation of innate immunity via controlling chromatin status and gene expression. [45][46][47] These chromatin modifiers perform coordinated actions to convert the extracellular stimuli into the complex gene expression patterns during innate inflammatory responses. At the steady state, the poised/inactive enhancers are occupied by lineage-determining transcription factors known as pioneers, such as PU.1 and marked with a combination of H3K4me1 and repressive H3K27me3.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…Epigenetic mechanisms such as DNA methylation, histone modifications and non-coding RNAs emerge to play essential roles in gene-specific transcriptional regulation of innate immunity via controlling chromatin status and gene expression. [45][46][47] These chromatin modifiers perform coordinated actions to convert the extracellular stimuli into the complex gene expression patterns during innate inflammatory responses. At the steady state, the poised/inactive enhancers are occupied by lineage-determining transcription factors known as pioneers, such as PU.1 and marked with a combination of H3K4me1 and repressive H3K27me3.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…Similar results have been obtained with BISPR (BST2 IFN-stimulated positive regulator). BISPR is a lncRNA induced by IFN [79][80][81] expressed from a bidirectional promoter that also drives BST2/tetherin. After IFN signaling, BISPR is expressed first, accumulates in the nucleus, and can act in trans to activate transcription of BST2, probably, by counteracting the suppressive role of PRC2 [80].…”
Section: Lncrnas Affecting the Expression Of Specific Isgs Located Nementioning
confidence: 99%
“…Likewise, Nishitsuji et al indicated that hnRNPU binds and stabilizes lncRNA#32. This lncRNA further binds to activating transcription factor to induce ISGs transcription, and, thus, repressing viral replication (Nishitsuji et al, 2016).…”
Section: Immune Response Employs Long Noncoding Rnas Against Virusesmentioning
confidence: 99%